2017
DOI: 10.1038/s41598-017-00648-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of single human embryonic stem cells and their pairs: a quantitative analysis

Abstract: Numerous biological approaches are available to characterise the mechanisms which govern the formation of human embryonic stem cell (hESC) colonies. To understand how the kinematics of single and pairs of hESCs impact colony formation, we study their mobility characteristics using time-lapse imaging. We perform a detailed statistical analysis of their speed, survival, directionality, distance travelled and diffusivity. We confirm that single and pairs of cells migrate as a diffusive random walk for at least 7 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 14 publications
1
34
0
Order By: Relevance
“…After these gaps are completely filled, we observe in large colonies the emergence of collective effects driven by the constant pushing and pulling of cells which drive the smallest and newly divided individuals to cluster in patches within the colony. Since the analysed colonies were grown on Matrigel TM , their migratory effects are large (Wadkin et al, 2017(Wadkin et al, , 2018 and this could be a relevant factor in the spatial organisation of the cells within the colony. The continuous re-organisation of the colonies implies that neighbours are interchanged continually and consequently the cell population is continuously mixed; this directly influences the level of clonality within the colonies and the outcome of community effects that will furthermore influence the pluripotency achieved by the population (Chang et al, 2019;Nemashkalo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After these gaps are completely filled, we observe in large colonies the emergence of collective effects driven by the constant pushing and pulling of cells which drive the smallest and newly divided individuals to cluster in patches within the colony. Since the analysed colonies were grown on Matrigel TM , their migratory effects are large (Wadkin et al, 2017(Wadkin et al, , 2018 and this could be a relevant factor in the spatial organisation of the cells within the colony. The continuous re-organisation of the colonies implies that neighbours are interchanged continually and consequently the cell population is continuously mixed; this directly influences the level of clonality within the colonies and the outcome of community effects that will furthermore influence the pluripotency achieved by the population (Chang et al, 2019;Nemashkalo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Previous works within our group have demonstrated that isolated hESCs growing on Matrigel™ with mTESR1 media are highly motile (∼ 16.25 µm/h) and sensitive to the presence of nearby cells (Wadkin et al, 2017(Wadkin et al, , 2018. As these single cells proliferate and possibly aggregate with other cells, colonies are formed.…”
Section: Introductionmentioning
confidence: 93%
“…The bias in the Figure 12. (a) Single hESCs preferentially move along their elongation axis, at speed higher for a stronger elongation. (b) Cells separated by 70 µm or less move in a coordinated manner, whereas a wider separation implies independent biased random walk [33].…”
Section: Discussionmentioning
confidence: 99%
“…The lineage trees for these cells are provided in Ref. [33]. We define the time variable t as zero at the start of the image recording.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation